FRAU.MACHT.RECHT.: 100 Jahre Frauen in juristischen Berufen - Dux, Elisabeth; Groß, Johanna; Kraft, Julia; Militz, Rebecca; Ness, Sina (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
A law of 11 July 1922 gave women in Germany access to both state examinations and thus to the legal profession for the first time. Since then, women have shaped the law, dispensed justice and fought for justice for themselves and others. On the occasion of the 100th anniversary in 2022, the following questions were examined at an interdisciplinary conference for young academics at the University of Heidelberg: Which path led to the admission of women to the legal profession? Where do we stand 100 years later? What can and should still be achieved? The conference was organised by five female academic staff members of the Faculty of Law in cooperation with the Heinrich Böll Foundation Baden-Württemberg.With contributions byWiebke Blanquett, M.A., LL.M.; Dr. Gesche Brand; Pola Brünger; Elisabeth Dux; Johanna Groß; Charlotte Heppner; Julia Kraft; Jun.-Prof. Dr. Fabian Michl; Rebecca Militz; Johanna Mittrop, Maîtr. en droit (Paris II), LL.M. (London); Sina Ness; Lea Rabe; Jun.-Prof. Dr. Bettina Rentsch, LL.M. (Michigan); Susanna Roßbach; Dr. Aqilah Sandhu, AkadR’in a.Z.; Dr. Martin Schwamborn, AkadR a. Z. and Ida Westphal.